Structures and optical properties of zinc oxide nanoclusters: a combined experimental and theoretical approach - Orek, Cahit; Keser, Serhat; Kaygili, Omer; Zuchowski, Piotr; Bulut, Niyazi (Springer, 2023)
ContextIn this study, theoretical and experimental analysis of the electrical, optical, and structural properties of a wurtzite-like zinc oxide (ZnO) nanostructure has been done. To investigate how quantum confinement affects the optical characteristics, two distinct ZnO clusters in nanowire structures have been investigated. The [(ZnO)(55)(H2O)(4)] system's HOMO-LUMO band gap (BG) was calculated to be 2.99 eV, which is quite close to the experimental measurement. It was found that the BG decreases with the increase in the number of atoms in the cluster in connection with the quantum confinement in nanoclusters. In addition, the lowest excitation energy in TD-DFT calculations of the identical system is in fairly good agreement with the experimental value with a difference of 0.1 eV. We conclude that the CAM-B3LYP functional has highly successful in reproducing the experimental data reported in the present study and previously reported experimental data.MethodsThe geometrical optimization of two different sizes of ZnO clusters ([(ZnO)25(H2O)4] and [ZnO)55(H2O)4]) was performed using the CAM-B3LYP functional with no symmetry constraints applied in the gas phase. LANL2DZ basis sets were used for the Zinc (Zn) atom and 6-31G* basis sets for the O and H atoms. To determine their optical and electronic properties, excited state calculations of the pre-optimized structures were performed using the Time-Dependent DFT (TD-DFT) method. Multiwfn, Gaussum 3.0, and GaussView 5.0 programs were used to visualize the results.
Keywords: Zinc oxide; TD-DFT; Quantum confinement; Energy band gap; Density of states